Biomembrane Structure and Material Properties Studied With Neutron Scattering - Kinnun, Jacob J.; Scott, Haden L.; Ashkar, Rana; Katsaras, John (Frontiers in Chemistry, 2021)
Cell membranes, and their associated structures, are dynamical supra-molecular structures where many physiological processes take place. As a result, a detailed knowl- edge of their static structures and dynamic behaviors is necessary if we hope to better understand membrane biology. The structure-function relationship is a basic tenet in biology and one that has been pursued using a range of different experimental ap- proaches. In this review article we will discuss one approach, namely the use of neutron scattering techniques as applied, primarily, to model membrane systems composed of lipid bilayers. An advantage of neutron scattering, compared to other scattering tech- niques, is the deferential sensitivity of neutrons to hydrogen’s isotopes and the relative ease of altering the sample’s contrast, simply by substituting protium for deuterium. This property makes neutrons an ideal probe for the study of hydrogen-rich materials, such as biomembranes. Here we describe isotopic labeling studies of model and viable membranes and discuss impactful applications of neutron contrast variation in gaining unique insights into the structure and dynamics of membranes. We specifically focus on how small angle neutron scattering data is modeled using different contrast data and molecular dynamics simulations. We also present a summary of recent advances in neutron spin echo spectroscopy studies and the unique membrane mechanical data that can be obtained using this spectroscopic technique that is currently experiencing somewhat of a renaissance due to new models used to fit the data.